THE COMPARISON OF TRANSPORT MODES WITH GIVING SUSTAINABLE DEVELOPMENT OF SOCIETY - Barash, Yu. S.; Korzhenevych, I. P.; Lykhopek, P. O. (Science and Transport Progress, 2009)
The external costs of different types of transport and the necessity of their account at comparison of variants are considered.